Modeling Possible Cooling-Water Intake System Impacts on Ohio River Fish Populations - Elgin Perry; Greg Seegert; Joe Vondruska; Timothy Lohner; Randy Lewis (The Scientific World Journal)
To assess the possible impacts caused by cooling-water intake system entrainment and impingement losses, populations of six target fish species near power plants on the Ohio River were modeled. A Leslie matrix model was constructed to allow an evaluation of bluegill, freshwater drum, emerald shiner, gizzard shad, sauger, and white bass populations within five river pools. Site-specific information on fish abundance and length-frequency distribution was obtained from long-term Ohio River Ecological Research Program and Ohio River Sanitation Commission (ORSANCO) electrofishing monitoring programs. Entrainment and impingement data were obtained from 316(b) demonstrations previously completed at eight Ohio River power plants. The model was first run under a scenario representative of current conditions, which included fish losses due to entrainment and impingement. The model was then rerun with these losses added back into the populations, representative of what would happen if all entrainment and impingement losses were eliminated. The model was run to represent a 50-year time period, which is a typical life span for an Ohio River coal-fired power plant. Percent changes between populations modeled with and without entrainment and impingement losses in each pool were compared to the mean interannual coefficient of variation (CV), a measure of normal fish population variability. In 6 of the 22 scenarios of fish species and river pools that were evaluated (6 species × 5 river pools, minus 8 species/river pool combinations that could not be evaluated due to insufficient fish data), the projected fish population change was greater than the expected variability of the existing fish population, indicating a possible adverse environmental impact. Given the number of other variables affecting fish populations and the conservative modeling approach, which assumed 100% mortality for all entrained fish and eggs, it was concluded that the likelihood of impact was by no means assured, even in these six cases. It was concluded that in most cases, current entrainment and impingement losses at six Ohio River power plants have little or no effect at the population level.